The Association Between Executive Functioning and Personal Recovery in People With Psychotic Disorders. Issue 1 (7th March 2022) - van Aken, B C; Wierdsma, A I; Voskes, Y; Pijnenborg, G H M; van Weeghel, J; Mulder, C L
Abstract: Background: Recovery in psychotic disorder patients is a multidimensional concept that can include personal, symptomatic, societal, and functional recovery. Little is known about the associations between personal recovery (PR) and functional recovery (FR). FR involves a person's ability to recover or compensate for impaired cognition, such as executive functions, and the loss of skills. Method: In this cross-sectional study (the UP'S study), we used measures of executive functioning and personal recovery to assess a cohort of people with a psychotic disorder. PR was measured using the Recovering Quality of Life (ReQOL) and Individual Recovery Outcomes (I.ROC). FR was assessed using two forms of assessment. The Behavioral Rating Inventory of Executive Functioning Adult version (BRIEF-A) was used for self-rated executive functioning, and the Tower of London (TOL) for performance-based executive functioning. Regression models were calculated between executive functioning (BRIEF-A and TOL) and PR (ReQOL and I.ROC). Model selection was based on the Wald test. Results: The study included data on 260 participants. While total scores of BRIEF-A had a small negative association with those of the ReQOL (β = −0.28, P > .001) and the I.ROC (β = −0.41, P > .001), TOL scores were not significantly associated with the ReQOL scores (β = 0.03, P = .76) and the I.ROC scores (β = 0.17, P = 0.17). Conclusion: Self-reported EF, which measures the accomplishment of goal pursuit in real life was associated with PR. However, processing efficiency and cognitive control as measured by performance-based EF were not.